1990
DOI: 10.1111/j.1365-2672.1990.tb02904.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Legionella pneumophila within cysts of Acanthamoeba polyphaga following chlorine exposure

Abstract: The association between Legionella pneumophila and the free-living amoeba Acanthamoeba polyphaga was studied. Intracellular growth of L. pneumophila within amoebic trophozoite was confirmed by kinetic growth experiments, light and electron microscopy. Cysts produced from infected trophozoites were found to protect the legionellas from at least 50 mg/l free chlorine. The ability of L. pneumophila to survive within the cysts of A. polyphaga is suggested as a possible mechanism by which the organism evades disinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
224
2
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(237 citation statements)
references
References 22 publications
6
224
2
5
Order By: Relevance
“…Amoebic trophozoites probably encyst in response to the disinfecting agents resulting in greater protection for the bacteria. In an equivalent study, Kilvington and Price (1990) reported cysts produced from co-cultures of Legionella with A. polyphaga protected the bacteria from 50 mg/L free chlorine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Amoebic trophozoites probably encyst in response to the disinfecting agents resulting in greater protection for the bacteria. In an equivalent study, Kilvington and Price (1990) reported cysts produced from co-cultures of Legionella with A. polyphaga protected the bacteria from 50 mg/L free chlorine.…”
Section: Discussionmentioning
confidence: 98%
“…The minimum residual chlorine concentration and contact time of 1 mg/L chlorine for 30 min, as prescribed by potable water providers in Australia, was insufficient to reduce a B. pseudomallei population by more than 2 log 10 Intra-protozoal growth of bacterial pathogens has been associated with increased environmental survival, enhanced virulence, and resistance to biocides and antibiotics (Kilvington and Price, 1990). Protozoa may serve as reservoirs for bacteria with human pathogenic potential (Marciano-Cabral and Cabral, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some bacteria, collectively referred to as amoebaresistant bacteria, resist amoeba phagocytosis (11). Some of them, such as Legionella pneumophila, are even able to multiply within amoeba trophozoites (23,29) and could be found within amoeba cysts (14,27). Intracellular L. pneumophila is more resistant to biocides (3,4,14).…”
mentioning
confidence: 99%
“…Some of them, such as Legionella pneumophila, are even able to multiply within amoeba trophozoites (23,29) and could be found within amoeba cysts (14,27). Intracellular L. pneumophila is more resistant to biocides (3,4,14). Consequently, free-living amoebae, such as Acanthamoeba, have been recently described as important targets in water treatment (19,30).…”
mentioning
confidence: 99%
“…Intracellular bacteria of freeliving amoebae such as Legionella pneumophila [21], Mycobacterium avium [22] or the Chlamydia-like organism, S. negevensis [9], can survive in the cysts and are localized within the cyst or between the cyst walls. With this in mind, we made the interesting observation that a small proportion of Cp.…”
Section: Encystment Assaysmentioning
confidence: 99%